2014
DOI: 10.1126/scitranslmed.3009688
|View full text |Cite
|
Sign up to set email alerts
|

Adult human neural crest–derived cells for articular cartilage repair

Abstract: In embryonic models and stem cell systems, mesenchymal cells derived from the neuroectoderm can be distinguished from mesoderm-derived cells by their Hox-negative profile--a phenotype associated with enhanced capacity of tissue regeneration. We investigated whether developmental origin and Hox negativity correlated with self-renewal and environmental plasticity also in differentiated cells from adults. Using hyaline cartilage as a model, we showed that adult human neuroectoderm-derived nasal chondrocytes (NCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 63 publications
3
77
2
2
Order By: Relevance
“…Recently, a new promising cell niche for articular cartilage regeneration was investigated by Pelttari et al 115 The authors showed that adult human neuroectoderm-derived nasal chondrocytes (NCs) can be constitutively distinguished from mesoderm-derived articular chondrocytes (ACs) by lack of expression of specific HOX genes, including HOXC4 and HOXD8. In contrast to ACs, serially cloned NCs could be continuously reverted from differentiated to dedifferentiated states, conserving the ability to form cartilage tissue in vitro and in vivo.…”
Section: Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Recently, a new promising cell niche for articular cartilage regeneration was investigated by Pelttari et al 115 The authors showed that adult human neuroectoderm-derived nasal chondrocytes (NCs) can be constitutively distinguished from mesoderm-derived articular chondrocytes (ACs) by lack of expression of specific HOX genes, including HOXC4 and HOXD8. In contrast to ACs, serially cloned NCs could be continuously reverted from differentiated to dedifferentiated states, conserving the ability to form cartilage tissue in vitro and in vivo.…”
Section: Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Other cell sources that have been considered are fat stromal cells and umbilical cord cells although no clinical trial has been published so far. An interesting approach using nasal septal cartilage that is derived from the neural ridge has been demonstrated to have good cartilage regenerating capacity in vitro and there are ongoing clinical trials with promising results [43].…”
Section: The Treatment Of Osteoarthritis and Cartilage Defectsmentioning
confidence: 99%
“…Nasal septal cartilage, previously labelled as the pacemaker for orofacial cartilage tissue regeneration (Pelttari et al, 2014) could potentially provide for an attractive non-disc source of cells as it contains a large population of differentiated chondrocytes (Kafienah et al, 2002). Nasal chondrocytes (NCs) (Bujia, 1995;Kafienah et al, 2002;Richmon et al, 2005) have been used to engineer cartilaginous constructs both in vitro and in vivo (Asawa et al, 2009;Candrian et al, 2008;Chia et al, 2005;Fulco et al, 2014;Hellingman et al, 2011;Malda et al, 2004;Richmon et al, 2005;Rotter et al, 2001Rotter et al, , 2002Scotti et al, 2012;Tsaryk et al, 2017;Twu et al, 2014;Watson and Reuther, 2014) and have recently been explored for nucleus pulposus tissue regeneration (Tsaryk et al, 2015;Tsaryk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%